2009
DOI: 10.1002/ppap.200932209
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Functionalized in Oxygen and Water Low Pressure Discharges used as Reinforcement of Polyurethane Composites

Abstract: The functionalization of multi‐walled CNTs in O2/Ar and H2O/Ar low pressure capacitive discharges was studied by XPS and FT‐IR. The pristine and functionalized CNTs were used as fillers in polyurethane paints. Successful plasma functionalization was confirmed by changes in atomic composition and chemical shift of the XPS atomic signals. The functionalization was indicated also by the shift of IR absorption peaks corresponding to the motion of carbon skeleton, especially the peak at about 1 560 cm−1. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Conditioned CNT-K (acidic treatment to remove the catalyst residue, washed afterwards to neutral conditions and stored in DI-water) showed a similar quantity of oxygen on the surface. Ndunda et al [56] and Zajíčková et al [57] reported comparable values to ours and suggested that these confirm the oxidation of the surface. Samples of CNT-K used as an electrode and treated several times in potential-controlled experiments showed an increase of the surface oxygen content (see Figures S7 and S8), due to redox reactions occurring on the surface, or other electrostatic or covalent molecule-surface interactions appearing during the experiments [58,59].…”
Section: Cnt-k Hydrophilicity and Surface Compositionsupporting
confidence: 85%
“…Conditioned CNT-K (acidic treatment to remove the catalyst residue, washed afterwards to neutral conditions and stored in DI-water) showed a similar quantity of oxygen on the surface. Ndunda et al [56] and Zajíčková et al [57] reported comparable values to ours and suggested that these confirm the oxidation of the surface. Samples of CNT-K used as an electrode and treated several times in potential-controlled experiments showed an increase of the surface oxygen content (see Figures S7 and S8), due to redox reactions occurring on the surface, or other electrostatic or covalent molecule-surface interactions appearing during the experiments [58,59].…”
Section: Cnt-k Hydrophilicity and Surface Compositionsupporting
confidence: 85%
“…The spectrum of as-prepared Ni@C (1) shows one C 1s peak at 284.5 eV with an asymmetric line shape attributed to sp 2 bonded carbon atoms in reference to the XPS studies of graphite 29 or carbon nanotubes. 30 The C 1s XPS spectrum of Ni@C (2) is more complicated and, in order to separate signals from functional groups, we have deconvoluted it into four peaks. As for Ni@C (1), the prominent peak at 284.5 eV reveals C-C interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma technology offers a new alternative to functionalize different types of nanoparticles, including carbon nanostructures, and promises to be an excellent technique due to its attributes of being versatile, fast, and enviroment friendly. One of the main applications of this technology is to promote the hydrophilization of carbon nanostructures using different sources of gases or monomers .…”
Section: Introductionmentioning
confidence: 99%